Neural correlates of executed and imagined joystick directional movements: a functional near-infrared spectroscopy study - Mathison, Matthew A., author; Rojas, Donald C., advisor; Davalos, Deana, committee member; Anderson, Chuck, committee member (Colorado State University. Libraries, 2019)
Motor-based brain computer interfaces (BCIs) attempt to restore and/or enhance motor functioning by measuring brain signals and converting them to computerized output. Functional near-infrared spectroscopy (fNIRS) is a non-invasive brain imaging modality that is resistant to both noise and motion-related artifacts. For this reason, fNIRS offers potential as an imaging method for use in a BCI. Currently, there is a paucity of literature on fNIRS as a sole BCI imaging method. Of the extant literature, studies were limited by low-density optode layouts and/or task designs which did not represent the motor goal. The present study was designed to enhance our understanding of the capabilities of fNIRS by utilizing a high-density optode array and an experimental task that closely mirrored the motor goal. 28 participants completed a series of executed and imagined joystick movements in four directions (forward, back, right, and left). Results indicated significant differences in inferred cortical activation during executed movements compared to baseline, executed movements compared to imagined movements, and imagined movements compared to baseline. No significant differences were observed for comparisons between individual movement directions. Results support the possibility that fNIRS may not be capable of distinguishing between changes in brain activity associated with joystick movement directions. Future research could enhance classification accuracy by implementing a machine learning algorithm or by pairing fNIRS with electroencephalography.
Keywords: fNIRS; motor; imagery; BCI